PENERAPAN MODEL PEMBELAJARAN TERBIMBING UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS I SDN 010 BANJAR PANJANG KECAMATAN KERUMUTAN - Sri Nurdiyati (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2016)
The background of this study was the low mathematics learning outcomes of first-grade students at SDN 010 Banjar Panjang, Kerumutan District. Out of 30 students, only 12 students (40.00%) achieved learning mastery. Therefore, this research was conducted by applying the guided learning model with the aim of improving students’ mathematics learning outcomes. This study was a Classroom Action Research (CAR) carried out in two cycles. The data used in this research focused on learning outcomes and the improvement of students’ learning mastery. The results of the study showed that the application of the guided learning model was able to improve students’ mathematics learning outcomes. This was evidenced by the increase in the number of students who achieved mastery, where in the preliminary data only 12 students (40.00%) achieved mastery, which increased in Cycle I to 20 students (66.67%), and further increased in Cycle II to 27 students (90.00%). It can be concluded that the guided learning model can improve the mathematics learning outcomes of first-grade students at SDN 010 Banjar Panjang.